Pengaruh Profitabilitas, Likuiditas, Struktur Aset, dan Pertumbuhan Penjualan Terhadap Struktur Modal pada Perusahaan Sektor Consumer Goods Industry yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2022 - Buana, David Imam; Karmawan; Anggita, Wenni (Jurnal EMT KITA, 2024)
This research aims to test and analyze the influence of profitability, liquidity, asset structure, and sales growth on capital structure in companies in the consumer goods industry sector. This type of research is quantitative research with a sample of companies in the consumer goods industry sector. The independent variables used in this research are profitability, liquidity, asset structure, and sales growth, while the dependent variable in this research is capital structure. The sample in this study was 32 companies using the purposive sampling technique. The data analysis method used is multiple regression analysis. Based on the results of research conducted with a sample of 32 companies, it can be concluded as follows: (1) The profitability variable has a significant positive influence on capital structure because the company is carrying out expansion which requires a lot of funds to encourage increased profits in the future. (2) The liquidity variable has a significant negative influence on capital structure because sector companies that have high liquidity means they can pay short-term debt, so they tend to reduce total debt, which ultimately will make the capital structure smaller. (3) The asset structure variable does not have an influence on the capital structure because most of the company's fixed assets are financed with the company's internal funds. An increase in fixed assets is not always followed by an increase in long-term debt. (4) The sales growth variable does not influence the capital structure because sales tend not to be supported by an efficient increase in the company's capital, resulting in operational costs that are too high